Circular Economy in Waste Bank for Sustainability and Empowerment - warsiyah; Mawardi; Moh Fahrurozi (Universitas Negeri Semarang, 2025)
This research aims to develop an integrative conceptual model that connects the circular economy, waste bank optimization, community empowerment, and sustainable economy. The novelty of this study lies in integrating digital incentive systems and participatory approaches in community-based waste management. The method employed was a mixed-methods approach, incorporating a quantitative component that utilized SEM-PLS on 200 respondents, complemented by qualitative data from in-depth interviews. The results indicate that community empowerment and the digitalization of waste bank systems have a significant impact on the sustainability of the local economy. Theoretically, this research strengthens the capabilities (Sen) and environmental economics (Pearce & Turner) approaches and practically offers a data-driven local policy framework for waste management optimization. The resulting model can serve as a reference for informed decision-making at the regional level, integrating environmental, social, and economic aspects sustainably.